Pelatihan teknologi informasi pada kantor kelurahan Barrang Caddi Kepulauan Sangkarrang - Nurul Aini; Erfan Hasmin; Heriadi Heriadi; Indra Samsie; Sitti Aisa; Muhammad Furqan Rasyid; Sriwahyuningsi Piu; Sunardi Sunardi; Sitti Harlina; Novita Sambo Layuk; Andi Asvin Mahersatillah Suradi; Arwansyah Arwansyah (Universitas Hamzanwadi, 2023)
As a public service provider, the sub-district office plays a crucial role in the issuance of referral letters and certificates. In this era of digitalization, effective and efficient administrative services are demanded, necessitating the improvement of staff knowledge and skills in information technology literacy. Hence, this community engagement activity aims to enhance the quality of administrative services by empowering human resources to operate computers and office applications at the Barrang Caddi Sub-district Office. The training program spans 3 days, encompassing Microsoft Word and Excel tutorials, as well as E-Mail usage. Enthusiasm was evident among the participants, which consisted of 7 sub-district office staff and 4 residents, as they actively engaged in the activities and completed the assigned tasks. The evaluation results demonstrate that the participants have comprehended and effectively applied the knowledge imparted during the training. The training materials have assisted the participants in optimizing their information technology knowledge and skills, such as efficiently managing administrative documents using Microsoft Office, operating E-Mail, and understanding the essential tools in Excel. This training validates the significance of information technology literacy efforts in sub-district office settings, particularly in areas with limited access to information. It is hoped that this community engagement initiative will continue and provide sustained benefits in enhancing administrative services and human resources quality at the Barrang Caddi Sub-district Office